A Case of Ivermectin-Induced Warfarin Toxicity: First Published Report. (December 2018) - Gilbert, Brian Wesley; Slechta, Joe
Here, we present the case of a patient who developed a large hematoma under his tongue while taking concomitant warfarin and ivermectin. Ivermectin has been shown to interfere with vitamin K–dependent clotting factors II, V, VII, and X. However, all the data to date have been from in vivo data with little to no reports on its effects on humans. To our knowledge, this is the first case report to present such a case.